Penggunaan WhatsApp dalam Penerimaan Reservasi Kamar di Jumana Bali Ungasan Resort - I Gusti Agung Mirah Sanjiwani (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2023)
The Covid-19 pandemic has changed many things in operational at hotels, including accepting room reservations that use social media. WhatsApp as one of the social media owned by hotels is starting to be used to receive room reservations, instead of communicating with employees in hotel operations. This study aims to analyze the model of accepting room reservations via WhatsApp and the advantages and disadvantages of using this social media at Jumana Bali Ungasan Resort. The research used a qualitative descriptive approach and conducted interviews and literature studies. The model for receiving reservations via WhatsApp consists of requests from guests regarding prices and room availability, checking room availability and responding to guest requests, requesting guest e-mails, reconfirming and sending invoices to e-mails, recording room bookings in the system, and sending confirmation letters to visitor. The advantage of using social media is that communication can be established quickly with guests and the disadvantage is the need for additional efforts such as reconfirming by e-mail because it requires proof of correspondence.